Air quality study in open-pit quarries in general Roca, argentina - Paula Andrea Paez; Marisa Gloria Cogliati; Raúl Alberto Giacosa (Boletín Geográfico)
This research have the objetive propose a study methodology to evaluate air quality in a mining activity based on the confiability and analysis of meteorological, topographic and emission data, which are entered into the dispersion model. The methodology was applied to the emissions the particulate material with a size smaller than 10 μm (PM10) generated from the operation of open pit quarries, near General Roca town (Argentina); and then evaluates their dispersion and possible impact on human health and / or the environment. The seasonal variations of the dispersion were analyzed and the Gaussian dispersion model used is AERMOD. The results showed that PM10 dispersion in different atmospheric conditions and emissions in 2010, don ́t influence urban areas near quarries and don ́t that exceed the legal limit. From the analysis of the seasonal variations of the dispersion changes were observed in the extension of the plume and in the maximum hourly concentration, especially in the autumn and winter seasons. The results of the modeling (maximum hourly concentration values) were compared with aerosol concentration data, obtained by remote sensors; Resulting in a determination coefficient (R2 ~ 0.7). The proposed work methodology can be incorporated as a control tool in government agencies for the evaluation and management of air quality so as to prevent unsatisfactory scenarios.